Visualising the Pandemic Pivot: Using Evidence-based Practice to Capture and Communicate an Academic Library's COVID-19 Response. Issue 3 (3rd July 2021) - Thorpe, Clare; Howlett, Alisa
ABSTRACT: The COVID-19 pandemic required an agile and quick transformation of services in university libraries in the wake of government health directives. As an evidence-based library, engaging in the collection of evidence and reflective practice was a natural extension of the pandemic response. Once the critical response period had passed, staff at the University of Southern Queensland set about capturing the Library's pandemic response within the wider context of society, government, and university activities in the form of a timeline. The timeline served to document actions taken in a time of crisis, recognise the staff workload involved, acknowledge the milestones achieved, and identify new performance measures to evaluate the impact of COVID-safe services This article offers a lived experience of how a university library can apply an evidence-based practice approach to inform decisions and drive improvements to service delivery. The timeline activity was not just about documenting what the Library did and when. It generated a source of evidence which has proved to be a useful tool in planning the return to campus activities and informing decision making about 'COVID normal' service models.